2005
DOI: 10.7861/clinmedicine.5-1-33
|View full text |Cite
|
Sign up to set email alerts
|

Over-regulation of clinical research: a threat to public health

Abstract: -Clinical research is subject to increasing regulation by research ethics committees and research and development offices which are responding to social and political pressures, as well as to new legislation, both European and national, some of which is still being worked out. The resulting bureaucracy, expense and confusion are putting insuperable hurdles in the way of clinical research and clinical care is compromised. What research is still possible will only be done in large organisations and may even be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Overregulation and excessively burdensome requirements of R&D committees using different formats from ethics committees, together with almost unanswerable questions on costs, have discouraged enthusiastic clinicians. 5 In addition, the requirements of research councils and medical schools to form large research groupings to permit clinical research or obtain research grants are often inimical to the innovative and inquiring spirit of individual NHS clinicians.…”
Section: Obstructions To Nhs Researchmentioning
confidence: 99%
“…Overregulation and excessively burdensome requirements of R&D committees using different formats from ethics committees, together with almost unanswerable questions on costs, have discouraged enthusiastic clinicians. 5 In addition, the requirements of research councils and medical schools to form large research groupings to permit clinical research or obtain research grants are often inimical to the innovative and inquiring spirit of individual NHS clinicians.…”
Section: Obstructions To Nhs Researchmentioning
confidence: 99%
“…In others, such as the United Kingdom and New Zealand, there is no formal legal requirement to seek ethical approval for university-based research unless it is medical research or research in an area that is covered by legislation (human tissue and research involving people lacking the mental capacity to consent). A relatively complete listing of legislation governing research can be found in Office for Human Research Protection (OHRP) (2009). this apparent overregulation of research (see, for example, Warlow 2005;Stewart et al 2008;Sullivan 2008;Dyer and Demeritt 2008).…”
mentioning
confidence: 94%
“…This trend has been characterised by Charles Warlow as 'a threat to public health' . 14 Those who have promoted recent trends in regulation appear not to have considered the responsibilities of clinicians faced with uncertainties about the effects of treatments. The situation has never been more succinctly summarised than by the paediatrician Richard Smithells, who declared 30 years ago: 'I need permission to give a drug to half of my patients, but not to give it to them all' .…”
Section: Confronting Therapeutic Uncertainties Through Research Withimentioning
confidence: 99%